El régimen de ayudas públicas: características y ventajas en el proceso de recuperación económica en tiempos de pandemia COVID19 - Rodríguez Miguez, José Antonio (2022)
In this paper we address the regulation of public aid, its characteristics and advantages for economic recovery based on a necessary conceptual delimitation, its economic foundation and its different regulatory areas, focusing on its importance in the current context of crisis created by the pandemic of Covid-19.With this objective in mind, we will successively expose its regulation in three different areas: multilateral, regional and national.In its multilateral dimension, we will focus on the rules contained in the framework of the World Trade Organization (WTO), where we will make a critical review of its current situation and its possible reform, highlighting the unilateral response of the European Union, adopting its own rules to control subsidies from third party countries in the European market.Next, we will analyze the rules on public aid “State aid” contained in the “Treaty on the Functioning of the European Union (TFEU)”, highlighting the special temporary and exceptional measures adopted by the European institutions due to the current pandemic, both with regard to aid granted by the Member States, as well as the European aid intended to support those Member States for economic recovery. In a later section we will offer the Spanish domestic regulation on public aid, as well as the regulation currently being drafted by the British Parliament to regulate subsidies in United Kingdom after its exit from the European Union.We will conclude this paper with a final reflection on its advantages and difficulties in facing the challenge of economic recovery, based on the need for their eventual granting to be governed by criteria of economic efficiency in the administration of public resources that are transferred to the market, through public aid.